An Overview of the Rialto Real-Time Architecture - Barrerra, Joseph S. III; Forin, Alessandro; Jones, Mike; Leach, Paul J.; Rosu, Daniela; Rosu, Marcel-Catalin (1996)
The goal of the Rialto project at Microsoft Research is to build a system architecture supporting coexisting independent real-time (and non-real-time) programs. Unlike traditional embedded-systems real-time environments, where timing and resource analysis among competing tasks can be done off-line, it is our goal to allow multiple independently authored real-time applications with varying timing and resource requirements to dynamically coexist and cooperate to share the limited physical resources available to them, as well as also coexisting with non-real-time applications. This paper gives an overview of the Rialto real-time architecture as it is implemented today and reports on some of the early results obtained. In particular, it describes the use of time constraints, activities, CPU and other resource reservation, and the system resource planner, and how they work together to achieve our goal of providing a flexible, dynamic real-time computing environment.
SPIE Astronomy Telescopes and Instruments